A comparative study of lipid profile in patients with and without infective hepatitis - Naik, Hemlatha D.; Kubihal, Chandrashekar V. (International Journal of Research in Medical Sciences, 2019)
Background: Liver plays a central role in lipid metabolism. Liver carries out some important functions in lipid metabolism like liver facilitates the digestion and absorption of lipids by the production of bile, which contains cholesterol and bile salts synthesized within the liver de novo or from uptake of lipoprotein cholesterol, the liver has active enzyme system for synthesizing and oxidizing fatty acids and for synthesizing triacylglycerols and phospholipids, synthesis of the ketone bodies, it plays an integral part in the synthesis and metabolism of plasma lipoproteins. The objective was to compare lipid profile in patients with and without infective hepatitis. Methods: Hospital based cross sectional comparative study was carried out among 112 cases. The patients were divided as having infective hepatitis (69) called cases and not having infective hepatitis (43) called controls. Concentration of serum total cholesterol was determined by Carr and Drekter method. Concentration of serum HDL cholesterol was determined by Carr and Drekter method. Concentration of serum triglyceride level was determined by enzymatic end point peroxidase coupled method. Results: Total cholesterol, VLDL, LDL and triglycerides have been found to be significantly higher in cases of infective hepatitis compared to control. The HDL value was also significantly deranged i.e. significantly lower in cases compared to controls (p <0.05). Thus, it was clear that infective hepatitis deranges the lipid profile of the patients. Conclusions: Lipid profile can be used as sensitive indicators of hepatic function and may have diagnostic and prognostic importance in infective hepatitis.